Pemilahan Sampah Rumah Tangga di Perumahan Pucang Gading Demak - Atmanti, Hastarini Dwi; Firmansyah; Fitria, Shoimatul (Yayasan Sagita Akademia Maju, 2026)
Improper waste management will cause problems. This community service project aims to train residents of RT 10 RW 15 Perumahan Pucang Gading, Demak in waste sorting. The method used in this community service activity is Participatory Action Research (PAR), where residents are actively involved in community service activities. Waste sorting activities are mandatory and sanctions are imposed on residents who do not sort and deposit waste. Sanctions have been successful in boosting locals' interest in rubbish sorting. The money raised for community initiatives will come from the sale of sorted waste.